2021
DOI: 10.1021/acsami.1c07109
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Strategy to Inhibit Droplets Rebound on Pathogen-Modified Hydrophobic Surfaces

Abstract: The deposition and retention of pesticide sprays on the surface of hydrophobic plant leaves is a major agricultural challenge, and the deposition of hydrophobic surfaces caused by plant leaf diseases is also a major agricultural problem. Many recent studies have focused on evaluating the effect of adding surfactants to water rather than to pesticide solutions to increase the deposition and retention of spray liquids. Here, we report a strategy to solve the problem of deposition and retention by studying the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…43 The sample flow rate and transport efficiency were 0.37 mL min −1 and 3.8%, respectively. 140 Ce, 139 La and 56 Fe with a natural abundance of about 88.5%, 99.9% and 91.7% were monitored during the analysis. The time-resolved mode (TRA) was applied in SP-ICP-MS analysis and the dwell time was 3 ms, with a total time of analysis of 60 s. 44 Details of the instrumental parameters of SP-ICP-MS are described in Table S2.…”
Section: Sp-icp-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…43 The sample flow rate and transport efficiency were 0.37 mL min −1 and 3.8%, respectively. 140 Ce, 139 La and 56 Fe with a natural abundance of about 88.5%, 99.9% and 91.7% were monitored during the analysis. The time-resolved mode (TRA) was applied in SP-ICP-MS analysis and the dwell time was 3 ms, with a total time of analysis of 60 s. 44 Details of the instrumental parameters of SP-ICP-MS are described in Table S2.…”
Section: Sp-icp-ms Analysismentioning
confidence: 99%
“…53 However, leaf tissues of rice, maize and cucumber have rough surfaces with dense textures and very good hydrophobicity. [54][55][56] The sprays of NPs on the leaf surface of the hydrophobic plants slip off easily, limiting their potential to enter the plant. 34 The NBCFs of dosed leaves were further studied and are illustrated in Fig.…”
Section: Effect Of Enzyme On Npsmentioning
confidence: 99%
“…This means maximizing the contact time in the retraction stage, while reducing the contact time in the spreading stage so that such droplets can easily wet the surface. These processes for droplet bouncing involve very complex dynamic mechanisms, including surface energy ( E s ), kinetic energy ( E k ), potential energy ( E p ), and viscous dissipation energy ( E v ). , With the development of modern technology, these dynamic mechanisms have been revealed, and then it is possible to control the droplet bounce by adjusting the basic parameters that affect the dynamics . The deposition of solution on the surface depends not only on the bouncing property of the droplet but also on the wetting and spreading behavior of the droplet on the surface .…”
Section: Introductionmentioning
confidence: 99%
“…These processes for droplet bouncing involve very complex dynamic mechanisms, including surface energy ( E s ), kinetic energy ( E k ), potential energy ( E p ), and viscous dissipation energy ( E v ). , With the development of modern technology, these dynamic mechanisms have been revealed, and then it is possible to control the droplet bounce by adjusting the basic parameters that affect the dynamics . The deposition of solution on the surface depends not only on the bouncing property of the droplet but also on the wetting and spreading behavior of the droplet on the surface . For the wetting and spreading behavior of droplets on artificial surfaces and plant leaf surfaces, most studies have focused on the static contact angle, surface tension, adhesion force, adhesion work, and so on; a few studies have also provided insights into the dynamic contact angle, contact angle hysteresis, adhesion force and wetting state (Young’s state, Wenzel state, Cassie state, Cassie–Baxter state).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical pesticide plays an important role in the control of pests for the security of food production 1 . Studies showed that nearly 50% of pesticides were lost in the process of leaf spray due to bounce and splash in the target crop leaves 2,3 , which brought about various issues by the loss of chemical pesticides [4][5][6][7][8][9][10] . Enhancing the pesticide droplet deposition on the target leaf is an effective strategy to decrease pesticides loss, and the issue has been extensively studied in recent years [5][6][7][8][9][11][12][13] .…”
mentioning
confidence: 99%